Pain and the endogenous antinociceptive neuronal system: physiologic role of oxytocin - Valença, Marcelo Moraes; Andrade-Valença, Luciana Patrízia A.; Antunes-Rodrigues, José (Headache Medicine, 2011)
The unpleasant pain sensation is a sub-modality of somatic sensation that exerts fundamental warning and protective functions. Pain is the more frequent complain in a neurological outpatient clinic. In a series of 200 consecutive patients in a neurological outpatient clinic, 51% of them complained of some type of pain, the more frequents were headache and carpal tunnel syndrome. The role of oxytocin in pain regulation was reviewed. It seems that oxytocin may play a major role in the mechanism of pain regulation, particularly through the endogenous antinociceptive neuronal system.